2015
DOI: 10.3109/09687637.2015.1050997
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive, psychosocial and functional status of individuals with alcohol-related brain damage (ARBD) on admission to specialist residential care

Abstract: Alcohol-related brain damage (ARBD) is a complex neuropsychiatric condition with a multifaceted impact on functioning and the ability to live independently. A comprehensive approach to assessing ARBD is therefore necessary. This study aimed to investigate the neurocognitive, psychosocial and everyday functioning of a group of individuals with ARBD on admission to specialist residential care. A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Consonant with the studies included in the first phase of extraction, the majority focused on KS participants ( n = 39), with few investigating ARD ( n = 4), ALC ( n = 4) or those with a diagnosis of ARBD ( n = 2). Adding to the confusion surrounding the use of ARBD as a specific diagnosis that was highlighted in the introduction, neither of the two studies which assessed participants with this diagnosis (i.e., Welch et al, 1997; Horton et al, 2015b) presented criteria for the condition or clearly described the definition of ARBD which they adopted. However, it appears that Welch et al (1997) used the term to refer to milder neurocognitive impairment not meeting criteria for WKS, while Horton et al (2015b) used the term more broadly; though it is unclear whether this included individuals with WKS diagnoses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consonant with the studies included in the first phase of extraction, the majority focused on KS participants ( n = 39), with few investigating ARD ( n = 4), ALC ( n = 4) or those with a diagnosis of ARBD ( n = 2). Adding to the confusion surrounding the use of ARBD as a specific diagnosis that was highlighted in the introduction, neither of the two studies which assessed participants with this diagnosis (i.e., Welch et al, 1997; Horton et al, 2015b) presented criteria for the condition or clearly described the definition of ARBD which they adopted. However, it appears that Welch et al (1997) used the term to refer to milder neurocognitive impairment not meeting criteria for WKS, while Horton et al (2015b) used the term more broadly; though it is unclear whether this included individuals with WKS diagnoses.…”
Section: Resultsmentioning
confidence: 99%
“…The CANTAB computerized battery assessment was investigated by one of the included studies. Horton et al (2015b) found those with ARBD were impaired relative to norm scores on various CANTAB tests, particularly the Rapid Visual Processing (RVP) test of sustained visual attention; though the authors suggest this may reflect a processing speed deficit rather than one of attention. Floor effects were also observed on the RVP, suggesting this test may be limited in assessing the spectrum of ability in those with ARCI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cognitive deficits can be associated with increased impulsivity (Bates et al, 2002;Czapla et al, 2016;Moraleda Barreno et al, 2019) that alter decision making (Domínguez-Salas, Díaz-Batanero, Lozano-Rojas, & Verdejo-García, 2016; Moraleda Barreno et al, 2019;Stevens et al, 2015). As a consequence, patients with alcohol-related cognitive impairment (ARCI) present lower self-efficacy (Bates, Pawlak, Tonigan, & Buckman, 2006;Sachdeva et al, 2016), lower motivation and treatment compliance (Bates et al, 2013(Bates et al, , 2006Bernardin et al, 2014), as well as fewer days of abstinence (Florez et al, 2019;Sachdeva et al, 2016), more drinks per drinking day (US SDUs, 1SDU = 14 g) (Bates et al, 2006) and poorer quality of life (Horton, Duffy, & Martin, 2015;Rensen, Egger, Westhoff, Walvoort, & Kessels, 2017). Furthermore, the comorbidity of ARCI with other psychiatric disorders, depression for instance, can worsen the cognitive symptoms (Horton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, despite the potential indirect effects of cognitive impairment in treatment outcome (Bates et al, 2002(Bates et al, , 2006Manning et al, 2017), ARCI is still underdiagnosed (Hayes et al, 2016;Horton, Duffy, & Martin, 2014;Soler González et al, 2014), under-recognised (Sachdeva et al, 2016) and undertreated (Barrio et al, 2016;Horton et al, 2015;Manning et al, 2017).…”
Section: Introductionmentioning
confidence: 99%